A novel animal model for subcutaneous soft tissue infection using temporally neutropenic lys-EGFP mice - Zulaziz, N.; Azhim, Azran; Miyazaki, H.; Kinoshita, M.; Himeno, N.; Saitoh, D.; Morimoto, Y. (2015)
Neutrophils play an important role against bacterial infection, mainly methicillin resistant Staphylococcus aureus (MRSA). Therefore, we developed an animal model to simultaneously monitor bacterial colonization and neutrophil migration in vivo. Using lys-EGFP C57BL/6 mice, we initially rendered the mice temporally neutropenic using cyclophosphamide (CPM) treatment (300mg/kg or 375mg/kg). Later, bioluminescent MRSA (Xen31, PerkinElmer) were subcutaneously injected (1.0×107 CFU) into the dorsal skin of the neutropenic lys-EGFP mice. The mice were then administered either saline (control group), or vancomycin (66mg/kg, treated group) consecutively for three days. For the evaluation of MRSA activity and neutrophil accumulation, an in vivo imaging system (LAS-4000, GE) was performed. Our results demonstrated that vancomycin is capable of killing bacterial cells and it also promotes inflammation. In addition, the rate of neutrophil regeneration after being suppressed by CPM is dependent on the dose of CPM. We could conclude that vancomycin is capable of inducing inflammation but the effects of the drug could only be observed if the immune system is adequately suppressed.